Antibacterial activity of lupeol from the bark of Dehaasia cuneate (Lauraceae) - Andi Rifki Rosandy; Sumail Sidik Ode Ishak; Noor Aziiraa Sabri; Wan Yaacob Wan Ahmad; Laode Muhammad Ramadhan Al Muqarrabun (Current Research on Bioscences and Biotechnology, 2021)
Dehaasia cuneata, locally known in Malaysia as ‘gajus hutan or pekan’, belongs to family Lauraceae. From its bark, A triterpenoid, lupeol was isolated and characterized. The chemical structure of the isolated compound was determined using spectroscopic methods, such as UV–vis, FT-IR, 1D & 2D-NMR, and ESIMS spectrometer. The isolated compound was tested against Gram-negative and positive bacteria using agar disc diffusion technique. The results showed that lupeol had a moderate inhibition zone value of 10.0±0.00 mm against Gram-negative Serratia marcescens ATCC 14756 whereas low inhibition which is 7.0±0.00 mm against Escherichia coli ATCC 25922, Vibrio fluvialis ATCC 33809, Bacillus subtilis ATCC 6633, and Methicillin-resistant Staphylococcus aureus (MRSA) ATCC 43300.